2008
DOI: 10.1038/nmeth.1255
|View full text |Cite|
|
Sign up to set email alerts
|

Tracking the structural dynamics of proteins in solution using time-resolved wide-angle X-ray scattering

Abstract: We demonstrate tracking of protein structural changes with time-resolved wide-angle X-ray scattering (TR-WAXS) with nanosecond time resolution. We investigated the tertiary and quaternary conformational changes of human hemoglobin under nearly physiological conditions triggered by laser-induced ligand photolysis. We also report data on optically induced tertiary relaxations of myoglobin and refolding of cytochrome c to illustrate the wide applicability of the technique. By providing insights into the structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
310
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 251 publications
(326 citation statements)
references
References 31 publications
11
310
1
Order By: Relevance
“…Our interpretation does not deviate from the previous femtosecond Fe K-edge XANES measurements on [Fe(bpy) 3 ] 2+ by Bressler and co-workers 12 and Fe L-edge XANES measurements of a related Fe spin-crossover complex Fe[(tren(py) 3 )] 2+ by Huse and co-workers. 14 Both studies showed instrument response time-limited dynamics for the formation of the HS excited state.…”
Section: As Shown Insupporting
confidence: 53%
See 1 more Smart Citation
“…Our interpretation does not deviate from the previous femtosecond Fe K-edge XANES measurements on [Fe(bpy) 3 ] 2+ by Bressler and co-workers 12 and Fe L-edge XANES measurements of a related Fe spin-crossover complex Fe[(tren(py) 3 )] 2+ by Huse and co-workers. 14 Both studies showed instrument response time-limited dynamics for the formation of the HS excited state.…”
Section: As Shown Insupporting
confidence: 53%
“…We performed the femtosecond X-ray absorption near edge structure (XANES) measurements on a 50 mM aqueous solution of [Fe(bpy) 3 ]Cl 2 at the XPP station of the LCLS (Figure 2). The experiment used a 0.1 mm thick liquid jet oriented at an angle of 45°with respect to the direction of the incident X-ray beam.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…3 It was also demonstrated that Mb shows a detectable difference scattering curve at the time delay of 10 ns upon the CO photolysis of carbonmonoxy Mb (MbCO), as shown in Figure 1A. This result for Mb is significant for the following reason.…”
mentioning
confidence: 80%
“…In one notable example, DEER experiments using spin-labeled frozen samples (T = 60 K) of the photoactive yellow protein showed that the distance distribution of the labels changed on exposure of the photoreceptor to light (Ramachandran et al 2011). In the same study, timeresolved pump-probe x-ray scattering (TR-SAXS/WAXS) (Cammarata et al 2008) was used to demonstrate that the radius of gyration and particle size both increased when the protein was exposed to light (Ramachandran et al 2011). Chemical shift perturbations and classical NOE data were combined with TR-SAXS/WAXS and DEER data to produce a model of the protein's dynamic light-exposed state (Ramachandran et al 2011).…”
Section: Integration Of Nmr With Other Analytical Methodsmentioning
confidence: 99%